PENYULUHAN KESEHATAN GIZI SEIMBANG SEBAGAI TINDAKAN PREVENTIF TERHADAP OBESITAS REMAJA DI DESA KAPEDI KECAMATAN BLUTO SUMENEP - Tawvicky Hidayat; Moh. Wardi; Encung Encung (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2023)
Obesity (over nutrition) is a very dangerous problem that is increasing every year. This is due to the ignorance of adolescents to maintain a lifestyle with balanced nutrition, and also the factor of a lazy lifestyle (lazy to move) which has recently become increasingly entrenched among adolescents. Especially with the existence of "cellphone" technology that makes humans increasingly suffer from diseases. Obesity is alcohol content of fat due to high cholesterol due to the conflict of incoming energy and outgoing energy. The causes of obesity are partly due to unbalanced fatty foods and lack of exercise. One of the problems in Kapedi village is the problem of obesity, where some people in this village are obese, and in fact it is a problem experienced by many villagers. For this reason, with the momentum of the National Nutrition Health Day, they held Nutrition Health counseling for adolescents. Servants choose teenagers because teenagers are the successor generation who will later become adults, secondly, teenagers are an educated generation whose thoughts are still clean so they need to change their mindset in terms of awareness. Teenagers are also the beginning of adulthood, which is the initial stage of obesity. For this reason, the servant held nutrition counseling which was divided into two stages, namely the first stage was the provision of knowledge about nutritional health, and the second stage was counseling about the dangers of obesity.